Synthesis and Antidiabetic Activity of Some New Furochromonyl-2,4-thiazolidinediones - Bozdagǵ-Dündar, Oya; Verspohl, Eugen J.; Waheed, Abdul; Ertan, Rahmiye (Arzneimittelforschung, 2003)
A new series of furochromone-2,4-thiazolidinedione derivatives (VIIa−h) was prepared by Knoevenagel reaction of substituted-2,4-thiazolidinediones (VIa−h) with Khellin-2-carboxaldehyde (IV ). The prepared compounds were tested for their insulinotropic activities in INS-1 cells. Compounds VIId and VIIf (at lower concentration; 1 µg/ml) were able to increase insulin release in the presence of 5.6 mmol/l glucose. Both these compounds (VIId and VIIf ) and VIIg increased glucose uptake in NIH-3T3 cells. Thus these 3 compounds should be tested for antidiabetic effects in vivo.
Keywords: Furochromones; Furochromonyl-2,4-thiazolidinediones, antidiabetic activity in vitro, synthesis; Khellin